Overexpression of Fli-1 is Associated with Adverse Prognosis of Endometrial Cancer. (21st October 2015) - Song, Wei; Zhang, Tianyang; Li, Wei; Mu, Rui; Zhang, Lingyi; Li, Yan; Jin, Baofeng; Wang, Na; Li, Ailing; Cui, Jiuwei
Abstract : This study aimed to investigate the expression of Friend leukemia virus integration 1 (Fli-1) and its correlation with the prognosis of endometrial cancer (EC). Thirty-two EC tissue samples were evaluated for Fli-1 expression using immunohistochemistry. Fli-1 showed significantly high expression in EC cells, followed by hyperplasia cells, and was negative in adjacent normal tissues. The high expression of Fli-1 was significantly associated with a high differentiation grade, mutated P53 expression, and histological subtype ( p < .05). Downregulation of Fli-1 in AN3CN cells using RNA interference inhibited cell clone formation and proliferation but did not affect apoptosis and migration of the cells. This study provides the first evidence that Fli-1 expression gradually increases in parallel with disease progression, and its overexpression might predict poor prognosis in EC.